How do you solve -6( 1+ 4x ) = 22+ 4x?

1 Answer
Nov 14, 2017

x=-1

Explanation:

First we will distribute parentheses/brackets using x(y+z)=xy+xz.

Therefore,
-6(1+4x) is the same as -6*1-6*4x.

-6*1=-6 and 4*6x=24x.

Whole equation now:
-6-24x=22+4x

Add 6 to both sides:
-6-24xcolor(red)+color(red)6=22+4xcolor(red)+color(red)6
Simplify:
-24x=4x+28

Subtract 4x from both sides:
-24xcolor(red)-color(red)4color(red)x=4x+28color(red)-color(red)4color(red)x

Simplify:
-28x=28

Now, we divide both side by -28.
(-28x)/-28=28/-28

Which is equal to x=-1.

Final answer:
x=-1.